Screening of lactic acid bacteria strains with urate‐lowering effect from fermented dairy products. Issue 11 (17th October 2022) - Zhu, Jun; Li, Yanjun; Chen, Zuoguo; Gao, Kan; Lin, Guodong; Chen, Su; Li, Li; Ge, Hongjuan
Abstract : Abstract: Hyperuricemia is a well‐known cause of gout and also a risk factor for various comorbidities. Current agents like xanthine oxidase inhibitors prevent hyperuricemia, but usually induce severe side effects. Alternative strategies, such as novel dietary supplementations, are necessary for the management of hyperuricemia. Lactic acid bacteria (LAB) have been used in human diet for a long time with a good safety record. In this study, 345 LAB strains isolated from traditional fermented dairy products were tested for assimilating abilities of guanosine. Two LAB strains, Lacticaseibacillus rhamnosus 1155 (LR1155) and Limosilactobacillus fermentum 2644 (LF2644), showing great capacities of guanosine transformation and degradation were selected. Compared to LR1155, LF2644 showed a better effect with 100.00% transforming rate and 55.10% degrading rate. In an in vivo test, a hyperuricemic rat model was established and the results showed that administration of LR1155 ( p < 0.01) or LF2644 ( p < 0.01) prevented the rise of serum uric acid with more than 20% decrease when compared with the hyperuricemia rats. In addition, an increased fecal uric acid level was observed in LF2644 or LR1155 treated rats (LR1155‐M p < 0.05, others p < 0.01). This study proved that LR1155 and LF2644 can be promising candidates of dietary supplements for prevention or improvement of hyperuricemia. Practical Application: The LAB strains tested in this study could be considered as good potential probiotic candidates for dietary supplements because of their urate‐lowering effects, which provide a novel antihyperuricemic strategy with advantages of safety and sustainability.